196k views
2 votes
6x + y = -1
-6x - 4y = 4
solve for x and solve for y

1 Answer

5 votes

9514 1404 393

Answer:

(x, y) = (0, -1)

Explanation:

The coefficients of x are opposites, so we can eliminate x by adding the two equations.

(6x +y) +(-6x -4y) = (-1) +(4)

-3y = 3 . . . . simplify

y = -1 . . . . . . divide by -3

Now, we need to find x.

6x -1 = -1 . . . substitute for y in the first equation

6x = 0 . . . . . add 1

x = 0 . . . . . . divide by 6

The solution is (x, y) = (0, -1).

User Grant Zukel
by
4.7k points